Effect of Investment Decision on the Profitability of a firm: Study on Manufacturing Company Listed on the Nigerian Stock Exchange - Ahmed, Ado; Ogbada, Michael Linus; Abdullahi, Adamu Aliyu (Kashere Journal of Management Sciences, 2024)
This study aims at examining the effect of investment decisions on the profitability of manufacturing firms listed on the floor of Nigerian stock exchange. Based on the study objectives, this is a causality research. The data used are secondary data for a 10-years period (2008-2017), obtained from Nigerian Stock Exchange fact book and the websites of the companies. The study employed a descriptive research design. The study adopted a census sampling approach because of the small number of companies under study. The study utilized panel data which was analyzed using regression model. Results revealed good, significant and positive correlations between ROA and all the predictor variables, that is, Investment Decision, Financial Leverage and Liquidity. The results further show that Investment decisions, financial leverage and liquidity affect company profitability positively and significantly. Based on the findings above the study recommends among others that corporate managers to provide avenues to increase their innovativeness and subsequent new investments, financial leverage, in particular their Debt-To-Equity ratio and their liquidity ratios in order to enhance profitability